Resting coronary flow drives the daily pattern in coronary flow reserve in patients with chest pain without obstructive epicardial stenosis - Thosar, Saurabh S.; Taqui, Sahar; Davidson, Brian; Belcik, Todd; Hodovan, James; Rice, Sean P. M.; Lindner, Jonathan R. (Frontiers in Cardiovascular Medicine, 2023)
Objectives Ischemia with no obstructive coronary artery disease (INOCA) is a risk factor for major adverse cardiovascular events and is characterized by abnormal coronary microvascular tone. In patients with INOCA, adverse cardiovascular events most commonly occur in the morning compared to other times of the day and night. Materials and methods We tested whether coronary microvascular function varies diurnally with attenuation in the morning in patients with symptomatic coronary artery disease without significant (>50%) epicardial stenosis. We evaluated data from 17 patients studied in the AM (700–1159 h) and 11 patients in the PM (1200–1800 h). Coronary microvascular function was measured using perfusion contrast imaging at rest and after infusion of intravenous regadenoson. We calculated microvascular flow reserve as the ratio of hyperemic to resting flow. Along with independent sample t-tests, we performed bootstrapping procedures to test mean differences between AM and PM groups, using the bias-corrected and accelerated method with 5,000 bootstrapped samples. Results and conclusion The AM and PM groups were matched for demographic and existing risk factors. Coronary microvascular flow reserve was ∼33% higher in the AM compared to the PM (P = 0.025, BCa 95% CI [0.25, 1.64]; Hedge’s g = 0.89, 95% CI [0.11, 1.66]) as a result of significantly lower resting flow (∼50%) in the AM compared to the PM (P = 0.03, MDiff = −56.65, BCa 95% CI [−118.59, −2.12]; Hedge’s g = −0.86, 95% CI [−1.60, −0.06]). Our observations are of clinical value and can influence diagnosis and treatment in the clinic based on the time of day of measurements.